2022
DOI: 10.1016/j.bioactmat.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Complete ablation of tumors using synchronous chemoradiation with bimetallic theranostic nanoparticles

Abstract: Synchronous chemotherapy and radiotherapy, termed chemoradiation therapy, is now an important standard regime for synergistic cancer treatment. For such treatment, nanoparticles can serve as improved carriers of chemotherapeutics into tumors and as better radiosensitizers for localized radiotherapy. Herein, we designed a Schottky-type theranostic heterostructure, Bi 2 S 3 –Au, with deep level defects (DLDs) in Bi 2 S 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The high-resolution Gd 4d XPS spectrum of Gd 2 O 3 @BSA-Au shows Gd 4d 5/2 and Gd 4d 3/2 spin–orbit peaks at the binding energies of 141.7 and 148.01 eV, respectively (Figure S2b). In the 4f high-resolution spectrum of gold, there are two peaks that correspond to the 4f 7/2 and 4f 5/2 of Au (0), respectively, with binding energies of 84.3 and 87.9 eV (Figure f). , The presence of C 1s peaks confirms the existence of BSA in the structure of Gd 2 O 3 @BSA and Gd 2 O 3 @BSA-Au NPs (Figure S2a,c).…”
Section: Resultsmentioning
confidence: 74%
“…The high-resolution Gd 4d XPS spectrum of Gd 2 O 3 @BSA-Au shows Gd 4d 5/2 and Gd 4d 3/2 spin–orbit peaks at the binding energies of 141.7 and 148.01 eV, respectively (Figure S2b). In the 4f high-resolution spectrum of gold, there are two peaks that correspond to the 4f 7/2 and 4f 5/2 of Au (0), respectively, with binding energies of 84.3 and 87.9 eV (Figure f). , The presence of C 1s peaks confirms the existence of BSA in the structure of Gd 2 O 3 @BSA and Gd 2 O 3 @BSA-Au NPs (Figure S2a,c).…”
Section: Resultsmentioning
confidence: 74%
“…The Fe 3 O 4 nanoparticles (IONPs) do not display a characteristic peak, whereas discernible absorption is observed in the spectrum of Bi 2 S 3 @BSA nanoparticles at 265 nm, which indicates the coating of BSA. [ 36 ] The same peak appeared at a higher wavelength for Bi 2 S 3 @BSA‐Fe 3 O 4 , indicating the interaction of Fe 3 O 4 with Bi 2 S 3 @BSA in the final structure. CUR shows a broad peak at 428 nm.…”
Section: Resultsmentioning
confidence: 90%
“…Therapeutic nanocarriers exhibit different therapeutic effects in different diseases, synergistically enter the tumour with chemotherapeutic drugs in vivo, and exhibit excellent CT imaging capabilities. 46 , 47 The X-ray attenuation property of CTPA@DOX was first examined in vitro to evaluate the potential of CTPA@DOX for CT imaging. It was observed that the higher the AuNP concentration, the more prominent the brightness of CT imaging ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%